Adenosine A1 Receptor-Mediated Synaptic Depression in the Developing Hippocampal Area CA2 - Caruana, Douglas A.; Dudek, Serena M. (Frontiers in Synaptic Neuroscience, 2020)
Immunolabeling for adenosine A1 receptors (A1Rs) is high in hippocampal area CA2 in adult rats, and the potentiating effects of caffeine or other A1R-selective antagonists on synaptic responses are particularly robust at Schaffer collateral synapses in CA2. Interestingly, the pronounced staining for A1Rs in CA2 is not apparent until rats are 4 weeks old, suggesting that developmental changes other than receptor distribution underlie the sensitivity of CA2 synapses to A1R antagonists in young animals. To evaluate the role of A1R-mediated postsynaptic signals at these synapses, we tested whether A1R agonists regulate synaptic transmission at Schaffer collateral inputs to CA2 and CA1. We found that the selective A1R agonist CCPA caused a lasting depression of synaptic responses in both CA2 and CA1 neurons in slices obtained from juvenile rats (P14), but that the effect was observed only in CA2 in slices prepared from adult animals (~P70). Interestingly, blocking phosphodiesterase activity with rolipram inhibited the CCPA-induced depression in CA1, but not in CA2, indicative of robust phosphodiesterase activity in CA1 neurons. Likewise, synaptic responses in CA2 and CA1 differed in their sensitivity to the adenylyl cyclase activator, forskolin, in that it increased synaptic transmission in CA2, but had little effect in CA1. These findings suggest that the A1R-mediated synaptic depression tracks the postnatal development of immunolabeling for A1Rs and that the enhanced sensitivity to antagonists in CA2 at young ages is likely due to robust adenylyl cyclase activity and weak phosphodiesterase activity rather than to enrichment of A1Rs.